Diversidad temporal de aves urbanas en los márgenes de los ríos Malacatos y Zamora de la ciudad de Loja - Tituana Medina, Wilmer Freddy (2023)
As a result of urbanization, global biodiversity is negatively affected and its biota is homogenized. Despite the evidence of urbanization's effects on urban avifauna and the responses of bird communities along urban gradients, little is known about the diversity and variability of bird communities in urban areas. Given their physical, chemical, and biotic heterogeneity, urban green spaces such as riverbanks are among the most diverse terrestrial ecosystems for the conservation of neotropical migratory species. The diversity and temporal distribution of birds along the banks of the Malacatos and Zamora rivers within the urban area of the city of Loja were evaluated. A total of 1237 individuals corresponding to 26 species and 19 families were identified through 36 counting points (18 on the Malacatos River and 18 on the Zamora River). The most recorded synanthropic species were Zenaida auriculata (Eared Dove), Furnarius leucopus (Pale-legged Hornero), Pygochelidon cyanoleuca (Blue-and-white Swallow) and Columba livia (Domestic Pigeon). The Kruskal- Wallis test indicated that there were no changes in abundance over the five months of sampling; however, there were significant differences in richness and diversity. There were no changes in species composition according to the analysis of similarity (ANOSIM). This may be due to two factors: (1) birds in the breeding season use their habitat in a more specialized and restrictive way due to their behavior; (2) the presence of highly persistent species (core species) that provide some temporal stability to the structure of a bird community. Using this information, helped gain a better understanding of the patterns and processes that biodiversity experiences in cities, which are crucial to the development of appropriate conservation measures.